Immobilization of Ochrobactrum sp. on Biochar/Clay Composite Particle: Optimization of Preparation and Performance for Nitrogen Removal - Sun, Pengfei; Huang, Xiao; Xing, Yixiao; Dong, Wenlong; Yu, Jianghua; Bai, Jie; Duan, Weiyan (Frontiers in Microbiology, 2022)
The objective of this study was to prepare biochar/clay composite particle (BCCP) as carrier to immobilize Ochrobactrum sp. to degrade ammonia nitrogen (NH4+-N), and the effects of calcined program and immobilizing material were investigated. Results reflected that the parameters were as follows: calcined temperature 400°C, heating rate 20°C min–1, and holding time 2 h, and the adsorption capacity could reach 0.492 mg g–1. Sodium alginate/polyvinyl alcohol, as embedding material, jointed with NH4+-N adsorption process and then degraded by Ochrobactrum sp. with 79.39% degradation efficiency at 168 h. Immobilizing Ochrobactrum sp. could protect strain from high salt concentration to achieve the exceeding degradation efficiency than free bacteria, but could not block the impact of low temperature.